Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Plastic occurrence, sources, and impacts in Antarctic environment and biota - Caruso, Gabriella; Bergami, Elisa; Singh, Neelu; Corsi, Ilaria (Water Biology and Security, 2022)
Several studies have documented that plastic pollution is affecting one of the most remote and pristine regions of our planet, Antarctica. Plastics of different size and polymeric composition have been retrieved in Antarctic sea ice, surface waters and sediments, with microplastics (mostly fibers) found both in terrestrial and marine organisms. Such evidence raises concerns about potential detrimental effects on biodiversity and ecosystem functions. The present review aims to report the most up-to-date knowledge on occurrence and distribution of plastic pollution in the Antarctic environment and biota including interaction with microorganisms, potential sources, and its impact on Antarctic biota. Our understanding of plastic pollution in this polar region will help us define the human footprint in Antarctica and predict future ecological risks.
Keywords: Sørishavet; forurensning; plastpartikler; økotoksikologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; fugler; miljøgifter; økotoksikologi

Spatial and interspecific variation of accumulated highly toxic trace elements between fifteen bird species feathers from Antarctic, Arctic and China - Sun, Yayue; Lu, Zhibo; Xiao, Kaiyan; Zeng, Lingyun; Wang, Juan; Zhang, Yanyun; Gabrielsen, Geir Wing (Environmental Technology & Innovation, 2022)
To assess the impact of human activities and other factors on the levels of highly toxic trace elements in the environment, the contents of eight highly toxic trace elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in feathers of 15 bird species from the Prydz Bay region in the Antarctic, Ny-Alsund region in the Arctic, and eastern China were evaluated in this study. Results showed that feathers collected from the Antarctic showed the highest As, Cu, and Hg contents (1.65–2.85, 9.58–18.56, and 4.77–8.76 μg/g dw, respectively) of the different study areas, whereas Arctic feathers exhibited the highest mean Pb levels (1.82–3.19 μg/g dw), and feathers from China showed significantly lower accumulations of Cr, Ni, Pb, and Zn compared with the other two areas. Overall, most of the studied highly toxic trace element contents in bird feathers from the densely populated and polluted area of eastern China were lower than those from remote polar regions, which are negligibly affected by human activities. In addition, feathers from the Arctic did not show higher highly toxic trace element contents than those of the more remote Antarctic. These results are thus inferred to reflect differences in the dietary structure of birds in the different habitats, as well as historical climate change. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of feathers were also measured to evaluate the relationship between diet and highly toxic trace elements. Results showed that highly toxic trace element contents did not increase with increasing trophic levels. Moreover, the methylmercury content accounted for 87.57%–98.59% of the total mercury in all feather samples, regardless of location and species, confirming that most of the mercury entering the feathers is methylated. This finding suggests that the form of mercury changes during the process of transference from internal tissues to feathers, which improves our understanding of the mechanism by which feathers excrete mercury, this behavior greatly reduces the harm to bird health caused by mercury. This study confirms that measuring contaminants in feathers is a long-term and effective method for monitoring highly toxic trace elements pollution in particular environments, making future monitoring of highly toxic trace elements pollution in the polar regions, as well as more typical environments, more convenient.
Keywords: Antarktis; miljøgifter; polarområdene; sjøfugler; økotoksikologi

Di(2-ethylhexyl) adipate (DEHA) detection in Antarctic krill (Euphasia superba Dana) - Han, Xiangning; Liu, Daicheng (Polar Research, 2018)
In this reported study, a novel high-performance thin-layer chromatography (HPTLC) method was developed for the detection and quantification of the toxic substance di(2-ethylhexyl) adipate (DEHA) in Antarctic krill. This procedure was based on the extraction of DEHA by ultrasonic solvent extraction with anhydrous ethanol, silica-gel column chromatographic separation, HPTLC detection and quantification using petroleum ether/ethyl acetate/ acetone/glacial acetic acid (29:1:0.5:2d*, v/v/v/v) as the developing solvent and bromine thymol blue solution as the chromogenic agent. The content of DEHA in freeze-dried Antarctic krill was found to be ca. 0.63 ± 0.05 mg/g. The structure of DEHA in the Antarctic krill was subsequently determined by gas chromatography–mass spectrometry (GC-MS) and infrared chromatography, which verified the presence of this compound in the krill. The HPTLC method exhibited excellent accuracy, with a recovery of 97.1–101.6% and good precision with a relative standard deviation of 2.47–4.90%. The DEHA in Antarctic krill oil was extracted by n-hexane and detected using the same method described above, which verified that DEHA was also present in krill oil at a concentration of ca. 2.16 ± 0.08 mg/g. The presence of DEHA in kill oil is very concerning because of its demonstrated harmful ecotoxicity, and since Antarctic krill is the key link in the food chain in the Antarctic coastal marine ecosystem. The adverse effects of DEHA on Antarctic krill and the source of DEHA will be explored in future research.
Keywords: Sørishavet; krill; marin forurensning; plankton; plastpartikler; økotoksikologi; økotoksiner